2022
DOI: 10.1136/openhrt-2021-001934
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in adherence to guideline recommendations for anticoagulation therapy in patients with atrial fibrillation and myocardial infarction

Abstract: BackgroundPoor adherence to guideline recommendations for anticoagulation in patients with acute myocardial infarction (MI) and atrial fibrillation (AF) is previously reported. The aim of the present cohort study was to assess time trends in prescription of anticoagulation therapy in a nationwide registry-based cohort of patients with acute MI and AF.MethodsAll patients, registered in the Norwegian Myocardial Infarction Registry (NORMI) between 2013 and 2019 with ECG-verified AF at hospitalisation, were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…AF has a negative impact on many cardiovascular diseases[ 106 , 107 ], but its most challenging is thromboprophylaxis. Although anticoagulation provides a net clinical benefit in patients with AF, a noticeable gap in antithrombotic prescription between real world and guideline recommendations was shown even in recent studies[ 108 - 111 ]. The long-awaited introduction of DOACs in the field of anticoagulation brought physicians a safer option, and in the last years, several real-world studies have confirmed their effectiveness and safety.…”
Section: Discussionmentioning
confidence: 99%
“…AF has a negative impact on many cardiovascular diseases[ 106 , 107 ], but its most challenging is thromboprophylaxis. Although anticoagulation provides a net clinical benefit in patients with AF, a noticeable gap in antithrombotic prescription between real world and guideline recommendations was shown even in recent studies[ 108 - 111 ]. The long-awaited introduction of DOACs in the field of anticoagulation brought physicians a safer option, and in the last years, several real-world studies have confirmed their effectiveness and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, when both coexist, it poses a significant threat to patients and a therapeutic challenge for physicians. Real-world data have shown that the triple antithrombotic therapy recommended by guidelines currently faces high bleeding risks and low compliance [ 5 ]. Therefore, there is a need to investigate more about the risk markers for NOAF after AMI in order to optimize risk stratification and improve prognosis.…”
Section: Introductionmentioning
confidence: 99%